Kool blue deodorant body spray in terms of marketing actions: a case study of Square Toiletries Limited - Bonik, Eric Mithun (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2017.